2021
DOI: 10.3390/f12121720
|View full text |Cite
|
Sign up to set email alerts
|

Logging Industry in the United States: Employment and Profitability

Abstract: This study analyzed logging industry employment and profitability in recent decades in the U.S. based on Occupational Employment Statistics (OES), Quarterly Workforce Indicators (QWI), Quarterly Census of Employment and Wages (QCEW), and Timber Product Output (TPO) Reports. The logging industry in the U.S. has experienced reduced employment with an aging workforce over the past two decades. The changes might be related to increased productivity from mechanization, combined with reduced demand for logging, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…In this scenario, the logging firms continued to produce to pay fixed costs, such as capital loans on equipment, while possibly incurring a loss. A similar trend was observed after the 2008 recession when, in the short term, logging firms would run without making profits if they could cover variable costs (He et al 2021). While not supported by efficient economics practice, the concept of "working harder and longer" in difficult times is a quite human response to a cash flow problem.…”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…In this scenario, the logging firms continued to produce to pay fixed costs, such as capital loans on equipment, while possibly incurring a loss. A similar trend was observed after the 2008 recession when, in the short term, logging firms would run without making profits if they could cover variable costs (He et al 2021). While not supported by efficient economics practice, the concept of "working harder and longer" in difficult times is a quite human response to a cash flow problem.…”
Section: Resultsmentioning
confidence: 76%
“…The literature suggests that the major challenges faced by the logging sector in the U.S. in the last 20 to 30 years are structural shortages of logging labor and rising operating costs (He et al 2021). At the same time, the effects of high fuel prices also have important ramifications in the workforce of logging contractors; for example, Moldenhauer and Bolding (2009) reported that the high fuel price led to a diminishing workforce.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing literature indicates that the primary obstacles encountered by the U.S. logging sector over the past two to three decades involve structural deficiencies in logging labor availability and escalating operational expenditures (He et al 2021). By addressing existing gaps in the literature and building upon previous research on efficiency in wood supply chains, this study contributes to the knowledge base essential for informed decision-making in the sector.…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, they play a vital role in the supply chain. Previous research points out that this critical link has gradually been weakened by the shortage of log truck drivers (Conrad IV, 2018; Gc et al, 2020; Koirala et al, 2016; Malinen et al, 2014) owing to a broad spectrum of structural factors, including decreasing profit margin (Casavant et al, 2009), increasing operating costs (He et al, 2021), variability in the availability of markets (Koirala & Kizha, 2017), lack of proper internal marketing strategies (S. L. Taylor & Cosenza, 1998), long waiting times in harvest sectors (Koirala et al, 2016), and high sawmill turnaround times (Conrad IV et al, 2018b). Most of these problems are interrelated, and decreasing profit margins result from multiple exogenous and endogenous factors (Conrad IV et al, 2018b) that the logging companies have limited control over, which we elaborate on below.…”
Section: Study I: Systematic Literature Reviewmentioning
confidence: 99%